Faster Atlantic currents drive poleward expansion of temperate phytoplankton in the Arctic Ocean - L. Oziel (Nature Portfolio, 2020)
The North Atlantic current has been suspected to trigger intrusions of temperate marine species in the Arctic. Here, Oziel and colleagues reveal the link between the poleward intrusion of the temperate coccolithophore Emiliania huxleyi and the North Atlantic current, showing evidence for bio-advection as an important mechanism.